Fit Evaluation during Repetition Interaction in Garment Pattern Design. (16th May 2019) - Zhu, Yuxiang; Peng, Yanjun
Abstract : We present a novel virtual try-on solution for fitting evaluation and pattern modification to design various types of garment and speed up the garment design process. In the phase of fit evaluation, we propose a method for producing two-dimensional (2D) color maps by comparing a 2D triangle mesh panel garment and a 3D triangle mesh garment, which can display the fit evaluation outcome in real time. In the phase of pattern modification, a novel prior condition based on maximum entropy coordinates and a more comprehensive mean value coordinates interpolation algorithm are proposed. By a combination of the two deformation methods, the positions of the internal vertices are updated smoothly. Applying the proposed method to the repetition of the garment design procedure, the experimental results show that it can easily pinpoint the location where it needs to be modified and can achieve arbitrary pattern modification with a smooth mesh update.